PENGGUNAAN TEKNOLOGI PARTIKEL NANO DALAM STIMULASI SUMUR DENGAN ALTERASI KEBASAHAN BATUAN - Fernando, Rizki
Nowadays nanoparticle are used as a new method for well stimulation and has a good potential in enhancing well performance by wettability alteration. Hydrophilic Silica Nano Structure Particle and Hydrophilic Silica Colloidal Nano Particle are two nanoparticle that will be discussed in this study. The objective of this study is to compare the two nanoparticles and what effect it will gives in term of increasing well performance also to determine which should be used in a sepcified reservoir rock properties. The result of data collection and experiments will be analysed and used to form a hypothesis of how to solve the problem in K-Field that thge production strats to decline even after appliyng Artificial Lift. Results show that the use of nano particles can change or alter the wettability of a core to a greater value or more water wet. With the altered wettability, oil residual saturation decreased and the oil relative permeability increased. Thus will make the well can produce more oil in a better desired rate. It also means that nano particle can increase the inflow performance relationship of a well.